1982
DOI: 10.1111/j.1365-2044.1982.tb01107.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced plasma cholinesterase following haemodilutional cardiopulmonary bypass

Abstract: SummaryThis case reporl presents a prolonged apnoea following the administration of suxarnethonium to a patient whose plasma cholinesterase concentrution was reduced as a consequence of haemodilutional cardiopulmonary bypass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…Plasma cholinesterase levels decrease by an average of 56% as a result of haemodilutional cardiopulmonary bypass and this persists for 7 days following surgery [65]. This is claimed to be due entirely to the priming of the bypass machine as opposed to such factors as temperature variations or absorption in the bypass tubing or in-line filters.…”
Section: Plasmapheresismentioning
confidence: 99%
“…Plasma cholinesterase levels decrease by an average of 56% as a result of haemodilutional cardiopulmonary bypass and this persists for 7 days following surgery [65]. This is claimed to be due entirely to the priming of the bypass machine as opposed to such factors as temperature variations or absorption in the bypass tubing or in-line filters.…”
Section: Plasmapheresismentioning
confidence: 99%
“…Há doenças que determinam decréscimo da atividade da colinesterase plasmática tais como hepatite, cirrose, colecistite, câncer com metástase a distância (principalmente de origem pulmonar, sistema genito-urinário e primário de intestino), desnutrição, insuficiência cardíaca grave, insuficiência renal, uremia e queimaduras extensas 9-12 . Ainda estão incluídas como causas de diminuição da atividade da pseudocolinesterase a plasmaférese, anticoncepcional oral, inibidores não competitivos da colinesterase (ecotiofato, organofosforados e ciclofosfamida), inibidores competitivos da colinesterase (neostigmina, edrofônio e piridostigmina), metoclopramida e pancurônio [13][14][15][16] . A metoclopramida inibe a colinesterase plasmática em até 70% do seu valor normal 3,17 .…”
Section: Discussionunclassified
“…S o m e d i s e a s e s d e t e r m i n e d e c r e a s e i n p l a s m a cholinesterase activity, such as hepatitis, cirrhosis, cholecystitis, cancer with distant metastasis (especially pulmonary, genito-urinary system and primary intestinal cancer), malnutrition, severe heart failure, renal failure, uremia and extensive burns 9-12 . Plasmaferesis, oral contraceptives, noncompetitive cholinesterase inhibitors (echothiophate, organop h o s p h o r a t e s a n d c y c l o s p h a m i d e ) , c o m p e t i t i v e cholinesterase inhibitors (neostigmine, edrophonium and pyridostigmine), metoclopramide and pancuronium are also responsible for pseudocholinesterase activity decrease [13][14][15][16] . Metoclopramide inhibits plasma cholinesterase in up to 70% of its normal value 3,17 .…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Jackson et al. (15) found that there was a decrease in plasma cholinesterase activity of approximately 56% during cardiopulmonary bypass as a result of haemodilution and the decreased level of plasma cholinesterase persisting for 7 days following surgery. The replacement solution used in our patient also had a contributory effect on depletion of plasma cholinesterase enzyme as a result of dilution.…”
mentioning
confidence: 97%
“…Although plasma cholinesterase levels were not determined in our patient, it is reasonable to assume that we managed anaesthesia in the presence of the effects of PP on plasma cholinesterase activity 5 days after the completion of multiple plasma exchanges based on previous reports (6,14,15). Naik et al.…”
mentioning
confidence: 97%